On Boundary Integral Equations of the First Kind (Journal of Computational Mathematics, 2022)
A large class of elliptic boundary value problems in elasticity and fluid mechanics can be reduced to systems of boundary integral equations of the first kind. This paper summarizes some of the basic concepts and results concerning the mathematical foundation of boundary element methods for treating such a class of boundary integral equations.